О возможности регулирования развития фитоценозов в техногенных экотопах Донбасса на основе сукцессионного подхода - Жуков, С.П. (Промышленная ботаника, 2006)
Generalized complex scheme of creating and regulating phytocenoses development in technogenic ecotopes on the base of succession approach with the separate stages studying is suggested. It is elaborated on the assumption of vegetation development of derelict lands. Suggested scheme can be modified for application to the very different conditions. Different sets of methods can be used, structure and width of investigetion can be changed in accordance with the aims and importance of works.